Mapping student enrolment and admission eligibility for higher education in Ethiopia: affirmative action as equity instrument? - Tesema, Melaku Tesfa; Blömeke, Sigrid; Braeken, Johan (Frontiers in Education, 2024)
IntroductionUNICEF’s Education For All steers for equal opportunities for all students and diversity in the student population. In Ethiopia, affirmative action is the policy tool addressing equity in enrolment and admission to higher education, targeting underrepresented groups such as females and students from emerging regions.MethodsIn a cross-sectional study across two-levels of education, regional differences in enrolment and admission eligibility were explored for two census student cohorts at high school (n = 858,557 and n = 785,053) and at the university preparatory program (n = 199,899 and n = 211,706). These population-level data stem from governmental registers from the mandatory national exams. Enrolment and admission eligibility statistics were computed with special attention to gender imparity. The impact of affirmative action was studied by comparison to the corresponding projected statistics computed as if affirmative action did not apply.ResultsIn most regions, clearly more male than female students were enrolled across the different educational levels. Affirmative action benefitted a significant percentage of female and emerging-region students. The gender parity in eligibility rates for admission to preparatory program for most regions was restored, but not for admission to university.DiscussionBeing implemented as policy directive for nearly three decades, affirmative action at most maintained gender imparity levels in enrolment inherited from earlier educational stages but failed in redressing inequity across gender and regions. Policy implications of the results and recommendations are discussed in light of regional differences and the currently implemented type of affirmative action.